A Facile Strategy for the Construction of Purely Organic Optical Sensors Capable of Distinguishing D2O from H2O. (2nd April 2019) - Luo, Yanju; Li, Chuan; Zhu, Wencheng; Zheng, Xujun; Huang, Yan; Lu, Zhiyun
Abstract: Owing to the quite similar chemical properties of H2 O and D2 O, rational molecular design of D2 O optical sensors has not been realized so far. Now purely organic chromophores bearing OH groups with appropriate p K a values are shown to display distinctly different optical responding properties toward D2 O and H2 O owing to the slight difference in acidity between D2 O and H2 O. This discovery is a new and facile strategy for the construction of D2 O optical sensors. Through this strategy, ratiometric colorimetric D2 O sensor of NIM‐2F and colorimetric/fluorescent dual‐channel D2 O sensor of AF were acquired successfully. Both NIM‐2F and AF can not only qualitatively distinguish D2 O from H2 O by the naked eye, but also quantitatively detect the H2 O content in D2 O. Abstract : Schweres Wasser sichtbar gemacht : Ein deprotonierungsbasierter Signalmechanismus für die Konstruktion optischer D2 O‐Sonden wird vorgestellt. Entwickelt wurden ratiometrisch‐kolorimetrische sowie fluorometrische Sonden, die in der Lage sind, qualitativ D2 O von H2 O mit bloßem Auge zu unterscheiden und den H2 O‐Gehalt in D2 O quantitativ zu bestimmen.